2008
DOI: 10.1016/j.brainresbull.2007.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the circadian system in zebrafish and the effects of melatonin on sleep and cognitive performance

Abstract: Aging is a complex process involving intracellular changes and, notably, modifications in intercellular communications, required for coordinated responses to internal and external events. One of the potential reasons for such changes is an age-dependent failure of the integrating systems, including the circadian clock. Here we demonstrate that aging in a diurnal vertebrate, zebrafish (Danio rerio), is associated with major but selective circadian alterations. By 3-5 years of age, zebrafish have reduced amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 35 publications
12
78
0
1
Order By: Relevance
“…Sleep (sleep-like behavior): Activity characterized in zebrafish by rest behavior, including reversible immobility/ hypolocomotion, elevated arousal threshold, reduced respiratory rate (e.g., opercular movements) and mouth opening frequency, and a compensatory rebound in response to sleep deprivation. 107,122,144,145,[153][154][155][156] In adult zebrafish, includes brief periods of inactivity, often with a drooping caudal fin (see Droopy tail), alternated with active periods of swimming; can be easily reversed by startling stimuli, such as tapping, sound, or weak electric field. 1.149.…”
Section: Sink (Sinking)mentioning
confidence: 99%
“…Sleep (sleep-like behavior): Activity characterized in zebrafish by rest behavior, including reversible immobility/ hypolocomotion, elevated arousal threshold, reduced respiratory rate (e.g., opercular movements) and mouth opening frequency, and a compensatory rebound in response to sleep deprivation. 107,122,144,145,[153][154][155][156] In adult zebrafish, includes brief periods of inactivity, often with a drooping caudal fin (see Droopy tail), alternated with active periods of swimming; can be easily reversed by startling stimuli, such as tapping, sound, or weak electric field. 1.149.…”
Section: Sink (Sinking)mentioning
confidence: 99%
“…3 ). They can be documented starting at 2 years of age and are associated with the gradual onset of melatonin deficiency and a decline in the expression of core clock genes [14,16] . An especially prominent decline was found in bmal1 mRNA abundance in aged zebrafish.…”
Section: Zebrafish As a New Vertebrate Animal Model Of Agingmentioning
confidence: 99%
“…Following the initial behavioral characterization of the sleep process in zebrafish and its modulation by melatonin, which we conducted in larvae [25] , we extensively investigated changes in sleep and circadian rhythms in aged zebrafish [14,26] . We found that in spite of the relatively long life span of this vertebrate, and its gradual senescence, sleep and circadian rhythmicity changes occur relatively early in life ( fig.…”
Section: Zebrafish As a New Vertebrate Animal Model Of Agingmentioning
confidence: 99%
“…Two groups of zebrafish (n = 10 fish per group), in triplicate, maintained with the photoperiod previously described, were exposed via water to two different doses of melatonin (Sigma Aldrich), 100 nM and 1 lM, following previous studies. 9,38 Briefly, for stock solution, melatonin was directly dissolved to 100 lM concentration in water. The actual levels of melatonin were confirmed by highperformance liquid chromatography with fluorescence detection using serial dilutions, in three independent experiments.…”
Section: Experimental Designmentioning
confidence: 99%